1984
DOI: 10.1002/ar.1092080113
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms of cell death and phagocytosis in the early chick lens morphogenesis: A scanning electron microscopy and cytochemical approach

Abstract: The cell surface characteristics of degenerating cells and phagocytes, as well as the participation of lysosomes in the cell death process associated with the early embryogenesis of chick lens rudiment, were studied by means of scanning electron microscopy and cytochemically using the Gomori-beta-glycerophosphate method for acid phosphatase. The prospective dying columnar epithelial cells lose their apical and basal processes and become rounded. The rounded, isolated, dying cells initially show a rough surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Consistent with this finding, lysosomal activation has been formerly reported to occur in the dying ectodermal cells (Garcia-Porrero et al, 1984).…”
Section: Cell Death In Superficial Epithelial and Mesodermal Tissuessupporting
confidence: 82%
“…Consistent with this finding, lysosomal activation has been formerly reported to occur in the dying ectodermal cells (Garcia-Porrero et al, 1984).…”
Section: Cell Death In Superficial Epithelial and Mesodermal Tissuessupporting
confidence: 82%
“…In addition, in the present study craters were occasionally observed on the surface of macrophages cocultured with apoptotic cells (Figures 2c and c 0 ). A mechanism of 'sinking-in craters' for internalization of apoptotic cells in early embryogenesis of the chick lens rudiment has been documented by Garcia-Porrero et al 35 This mechanism can be considered as a variation of the zipper model. 33 L929sAhFas cells treated with mTNF underwent necrosis; SEM showed that their surfaces were irregular, pointing to loss of the integrity of the plasma membrane ( Figure 3).…”
Section: Discussionmentioning
confidence: 94%
“…Concurrently with the flux of crest cells reaching the optic cup, a minor but essential progression of mesodermal cells occurs towards the interface between the superficial ectoderm and the lenticular vesicle leading to the differentiation of macrophage-like cells (Hay, 1980;Garcia-Porrero et al, 1984;Cuardos et al, 1991). These cells clean up the debris released by the apoptotic events associated with lens morphogenesis, a prerequisite for the deposition of a primary corneal stroma permissive for neural crest cell migration into the lensectoderm interspace (Hay, 1980).…”
Section: Discussionmentioning
confidence: 99%